Comparative study of joint can fatigue life - Kitinum Pongsapasiritut; Chiu, Gregory L.F.; Widjaja, Joko Harsono; Pennung Warnitchai; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
95% of offshore platforms all around the world including the Gulf of Thailand (GOT) are steel template jacket module due to the robustness and lower time of fabrication. Their characteristics such as exposing to cyclic environmental load and large localized stresses at joint intersections result in risk from fatigue failure mode. The objective of this research is to compare the fatigue strength in tubular joint cans of steel jacket platform according to updated provisions on API RP2A WSD 21st supplement 2 (2005). Three representative jackets on water depth as 191, 215 and 240 feet were modeled as space frame using SACS package program. Meanwhile, spectral fatigue analysis was performed through varied parameters consisting of joint thickness and diameter ratio, S-N curves and stress concentration factor formulas. The results are presented as relation of fatigue life ratio and joint geometries for T & Y, TK and K type. These relations are interpreted as the endurance limit significantly affects joint fatigue life. Furthermore, fatigue life can be exponentially increased or decreased by tubular joint geometries.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Offshore Technology and Management, School of Engineering and Technology
Thesis (M. Eng) - Asian Institute of Technology, 2011
Keywords: Steel -- Fatigue